2002
DOI: 10.1093/jjco/hyf079
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Six-nucleotide Insertion in Exon 4 of the MEN1 Gene, 878insCTGCAG, in Three Patients with Familial Insulinoma and Primary Hyperparathyroidism

Abstract: Three Japanese patients (a man and his two sons) in a family with clinical diagnosis of familial multiple endocrine neoplasia type 1 (MEN1) suffered from insulinoma(s), primary hyperparathyroidism and pituitary microadenoma. Genomic DNA of the patients was analyzed by sequencing for the MEN1 gene and an insertion of six nucleotides, CTGCAG, in exon 4, resulting in insertion of two amino acids, Leu-Gln, after the 256th amino acid of the menin (256insLQ), was identified. CTGCAG is a palindromic sequence and repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Okamoto et al . suggested that a novel six‐nucleotide insertion in exon 4 of the MEN1 gene might contribute to the familial insulinoma. A prior study indicated that MEN1 gene mutations were lacking in 27 sporadic insulinomas .…”
Section: Discussionmentioning
confidence: 99%
“…Okamoto et al . suggested that a novel six‐nucleotide insertion in exon 4 of the MEN1 gene might contribute to the familial insulinoma. A prior study indicated that MEN1 gene mutations were lacking in 27 sporadic insulinomas .…”
Section: Discussionmentioning
confidence: 99%